2022
DOI: 10.3390/catal13010074
|View full text |Cite
|
Sign up to set email alerts
|

Composite CdS/TiO2 Powders for the Selective Reduction of 4-Nitrobenzaldehyde by Visible Light: Relation between Preparation, Morphology and Photocatalytic Activity

Abstract: A series of composite CdS/TiO2 powders was obtained by nucleation of TiO2 on CdS nanoseeds. This combination presents the appropriate band edge position for photocatalytic redox reactions: visible light irradiation of CdS allows the injection of electrons into dark TiO2, increasing the lifetimes of separated charges. The electrons have been used for the quantitative photoreduction of 4-nitrobenzaldehyde to 4-aminobenzaldehyde, whose formation was pointed out by 1H NMR and ESI-MS positive ion mode. Concomitant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Yanagida and coworkers reported that several polychlorinated benzenes were dehalogenated using ZnS and CdS nanocrystals under UV and visible light irradiation, respectively, in the presence of triethanolamine as a sacrificial electron donor for the photogenerated holes [25]. Similar processes were studied also with CdS/TiO 2 nanocomposites, exploiting the demonstrated improvement of charge separation efficiency [26][27][28][29]. Core shell ZnSe/CdS quantum dots had been used for hydrogenation or arylation of aryl bromides under 455 nm irradiation with DIPEA (N,N diisopropylethylamine) as a sacrificial donor [30].…”
Section: Introductionmentioning
confidence: 98%
“…Yanagida and coworkers reported that several polychlorinated benzenes were dehalogenated using ZnS and CdS nanocrystals under UV and visible light irradiation, respectively, in the presence of triethanolamine as a sacrificial electron donor for the photogenerated holes [25]. Similar processes were studied also with CdS/TiO 2 nanocomposites, exploiting the demonstrated improvement of charge separation efficiency [26][27][28][29]. Core shell ZnSe/CdS quantum dots had been used for hydrogenation or arylation of aryl bromides under 455 nm irradiation with DIPEA (N,N diisopropylethylamine) as a sacrificial donor [30].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, in addition to poor activity under visible light irradiation, any large-scale application of TiO 2 nanoparticles (NPs) for water treatment is hampered by the tendency of titania NPs to agglomerate and by difficulties in NP separation after water treatment leading to poor catalyst recovery. [17][18][19][20] Consequently, numerous efforts are underway to (1) improve the photocatalytic response of TiO 2 under visible light, 21 (2) improve the ease of separation of the photocatalyst from a water body that has been treated, 22 and…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in addition to poor activity under visible light irradiation, any large-scale application of TiO 2 nanoparticles (NPs) for water treatment is hampered by the tendency of titania NPs to agglomerate and by difficulties in NP separation after water treatment leading to poor catalyst recovery. 17–20 Consequently, numerous efforts are underway to…”
Section: Introductionmentioning
confidence: 99%
“…therein [ 18 ], and the use of CdS-based photocatalysts for the photocatalytic reduction of CO 2 gradually has aroused a great interest from researchers in recent years [ 19 , 20 , 21 ]. They report that there are many factors that affect the efficiency of these reductive processes, including the morphology, crystal structure and composition; in addition, the synthetic method employed plays an important role in establishing and influencing the characteristics of the obtained material [ 22 ]. More generally, the location of the conduction band at negative potentials makes CdS a photocatalyst of interest for reductive transformations that take advantage of electrons promoted in the conduction band [ 23 ].…”
Section: Introductionmentioning
confidence: 99%